“O Love, in (Your) Delights” - Nikolas Kristiyanto (Litbang STFT Widya Sasana Malang, 2019)
The interpretation of the Song of Songs has a long history. The traditional Jewish and early Christian interpreters apply the allegory method to find a “spiritual” meaning. For example, they try to understand the Groom as the Lord and the Bride as Israel. Furthermore, early Christian tradition interprets the Groom as Jesus and the Bride as the Church. Nevertheless, in this article, we try to read the Song of Songs in other perspective by understanding it in the light of Ancient Near East (ANE)’s background. We will focus on the exegesisand general analysis on Song 7:7-10a. This passage is a part of a big section of Song 6:4-7:11 (“New Songs of the Beloved Man”). Song 7:7-10a is an admiration-movement. We try to propose a new general structure of Song 7:7-10a and its meaning in the light of ANE’s background on royal ideology, temple, wisdom, promised land and love traditions.